2022
DOI: 10.3389/fpsyg.2022.810015
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impact on Teachers’ Organizational Commitment in Schools

Abstract: Highly committed teachers spend more effort helping their schools achieve their academic goals. The COVID-19 pandemic had a dire effect on education worldwide. However, just after a few semesters, teachers were asked to return back to schools to teach in person. This study aims to analyze the organizational commitment levels of school teachers before and after the implementation of the COVID-19 pandemic measures that resulted in a two-semester break in face-to-face teaching. In this study, a quantitative resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…Overall, the findings have showed that the remote online education challenges found in this study has had negative impact on students' well-being (Holm-Hadulla et al, 2021;Lukacs, 2021). High stress, increased burn out and decreased organizational commitment were also observed among the teachers (Akartuna & Serin, 2022;Esici et al, 2021;Pressley et al, 2021). Drawing on this, research community and policy makers have come up with several remedies to tackle the challenges of remote online learning.…”
Section: Discussionsupporting
confidence: 50%
“…Overall, the findings have showed that the remote online education challenges found in this study has had negative impact on students' well-being (Holm-Hadulla et al, 2021;Lukacs, 2021). High stress, increased burn out and decreased organizational commitment were also observed among the teachers (Akartuna & Serin, 2022;Esici et al, 2021;Pressley et al, 2021). Drawing on this, research community and policy makers have come up with several remedies to tackle the challenges of remote online learning.…”
Section: Discussionsupporting
confidence: 50%
“…The instrument consisted of 21 items. It had the following indicators, namely: support (1-10); supervision (1-3); and coherent leadership team (1)(2)(3)(4)(5)(6)(7)(8). The questionnaire was subjected to a pilot testing having a result of .70 suggesting that the items have relatively high internal consistency.…”
Section: Research Instrumentsmentioning
confidence: 99%
“…Teachers encounter social and economic issues while providing online instruction. The COVID-19 pandemic's use of technology in the classroom inadvertently pushed teachers to instruct using digital tools without previous training (Hoang, 2020;Akartuna and Serin, 2022). The achievement of these reforms' objectives, namely the provision of the best possible educational services, is thus anticipated to depend on teacher acceptance of change.…”
Section: Introductionmentioning
confidence: 99%
“…To succeed in the planned change program, commitment to change is thought to be a key component of change management (Kayani et al, 2022). It is believed that teachers' commitment level was impacted by their degree of stress during the pandemic (Akartuna and Serin, 2022). A person's desire or attitude that ties them to a series of behaviors deemed necessary for the successful execution of change efforts is known as their commitment to change (Herscovitch and Meyer, 2002).…”
Section: Introductionmentioning
confidence: 99%